PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN LEMBAGA PENYIARAN PUBLIK (LPP) RRI SURAKRTA - Erna Tiningrum; Dewi Setyaningsih (KELOLA, 2018)
This study aims to determine and prove empirically the influence of leadership variables, work environment, work discipline on employee performance at Public Broadcasting Institutions (LPP) RRI Surakarta. Data is taken directly by giving a questionnaire to employees. Respondents in this study amounted to 98 employees. Analytical techniques in this study consisted of, instrument testing, asumsiklasik test, multiple linear regression analysis, t test, f test, and test R2. The results of this study prove the results of this research regression can show that all independent variables positively affect the employee performance on Public Broadcasting Institutions (LPP) RRI Surakarta. The result of t test shows that leadership and work environment variables significantly influence the performance of employees of Public Broadcasting Institution (LPP) RRI Surakarta, while the variable of work discipline has an insignificant effect on the performance of employees of RRI Surakarta Public Broadcasting Institution. The result of F test shows that there is a significant influence on leadership variables, work environment, work discipline together to the performance of employees at Public Broadcasting Institution (LPP) RRI Surakarta. The result of R2 test that the influence given by the variable of leadership, work environment, work discipline on employee performance is 40,9% while the rest 59,1% influenced by other variable not included in this research for example job satisfaction, organizational commitment, compensation .Keywords: Leadership, Work Environment, Work Discipline, Employee Performance.